Overcoming CDK4/6 inhibitor resistance in ER-positive breast cancer. Issue 1 (January 2019) - Portman, Neil; Alexandrou, Sarah; Carson, Emma; Wang, Shudong; Lim, Elgene; Caldon, C Elizabeth
Abstract : Three inhibitors of CDK4/6 kinases were recently FDA approved for use in combination with endocrine therapy, and they significantly increase the progression-free survival of patients with advanced estrogen receptor-positive (ER+) breast cancer in the first-line treatment setting. As the new standard of care in some countries, there is the clinical emergence of patients with breast cancer that is both CDK4/6 inhibitor and endocrine therapy resistant. The strategies to combat these cancers with resistance to multiple treatments are not yet defined and represent the next major clinical challenge in ER+ breast cancer. In this review, we discuss how the molecular landscape of endocrine therapy resistance may affect the response to CDK4/6 inhibitors, and how this intersects with biomarkers of intrinsic insensitivity. We identify the handful of pre-clinical models of acquired resistance to CDK4/6 inhibitors and discuss whether the molecular changes in these models are likely to be relevant or modified in the context of endocrine therapy resistance. Finally, we consider the crucial question of how some of these changes are potentially amenable to therapy.